Geographic predictors of early 20th century northern Albanian tribal demography - Elic M Weitzel; Erina Baci; Daniel Plekhov (Kosova Anthropologica)
As tribal social structures have long been prevalent in our species, understanding the drivers of tribal demography is of great importance. Here, we explore the potential effects of several geographic factors on population size among early 20th century northern Albanian tribes.Through a model comparison analysis of population data from forty-six tribes, we investigate how tribal population size was influenced by slope, net primary productivity, water availability, number of neighboring tribes, and distance to urban centers. Our results suggest that while slope and the number of neighboring tribes are the best available predictors, their overall ability to predict Albanian tribal population size in the early 20th century is poor. An unexplored factor such as tribal wealth (in terms of land, livestock, infrastructure, or marriage alliances) could be a more important driver of population size, but it is perhaps most likely that decades of conflict in the late 19th and early 20th centuries reshaped the demographic landscape of northern Albania and obscured any pre-existing geographic influences on tribal demography.